DEVELOPMENT PROSPECTS OF BIOPHARMACEUTICAL PLANTS IN PALEMBANG CITY - Meri Ariyantini; Mirza Antoni; R Riswani (BIOVALENTIA: Biological Research Journal, 2022)
Biopharmaceutical plants or medicinal plants are plants grown in the garden that have medicinal properties. The types of biopharmaceutical plants have been cultivated for more than 5 years and are managed by the people of Palembang City who are members of farmer groups and women's groups of biopharmaceutical plant farmers of galangal and lemongrass. Besides being consumed in a fresh form as a kitchen spice, it can also be processed as an addition to herbs, chips, and shredded galangal and can also work as a vegetable pesticide and fertilizer for plants. This study aims to see the prospects for the development of biopharmaceutical plants in the city of Palembang. The method used is a survey method, data collection is carried out directly through interviews using questionnaires. Data processing uses indicator analysis techniques based on, cultivation techniques and demand for biopharmaceutical plants in the last year, namely 2020 with 50 respondents, farmers of biopharmaceutical plants. The results of the analysis show that the survey of farmers' knowledge level of biopharmaceutical crops is 84%, cultivation technique capability is 78% and demand for biopharmaceuticals in 2020 will increase by 15% for galangal and 22% for dissolution in the previous year. Judging from the level of interpretation of the score of each indicator which is above 60% and the demand for biopharmaceutical plants has increased. That can be said the prospect of developing biopharmaceutical plants in Palembang City is promising.